2020
DOI: 10.1159/000511323
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer in <b><i>BRCA1</i></b> Germline Mutation Carriers: Results of Endoscopic Screening and Molecular Analysis of Tumor Tissues

Abstract: <b><i>Introduction:</i></b> There is some evidence suggesting a link between <i>BRCA1/2</i> germline mutations and increased risk of gastric cancer. <b><i>Methods:</i></b> Endoscopic screening for stomach malignancies was performed in 120 <i>BRCA1</i> mutation carriers in order to evaluate the probability of detecting the tumor disease. <b><i>Results:</i></b> No instances of gastric cancer were revealed at the first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…However, we identified an ERBB2 mutation at V842I, which is commonly found in colorectal cancer[ 21 ].We discovered that 15 patients carried BRCA1/2 mutations. The current study also demonstrated that GC or GEJ tumour patients carried BRCA1/2 mutations[ 22 ], which may be related to tumorigenesis, including GC development. A molecular analysis of BRCA1/2 mutations clearly revealed distinct categories of tumours[ 23 ].…”
Section: Discussionmentioning
confidence: 64%
“…However, we identified an ERBB2 mutation at V842I, which is commonly found in colorectal cancer[ 21 ].We discovered that 15 patients carried BRCA1/2 mutations. The current study also demonstrated that GC or GEJ tumour patients carried BRCA1/2 mutations[ 22 ], which may be related to tumorigenesis, including GC development. A molecular analysis of BRCA1/2 mutations clearly revealed distinct categories of tumours[ 23 ].…”
Section: Discussionmentioning
confidence: 64%
“…The colonized biotin-type DNA probe (GeneSeqOne TM ) was used to hybridize and capture 415 coding regions of genes related to gastric cancer and 16 introns of genes in the library. Meanwhile, the library DNA was amplified with the help of Illumina p5, p7 primers, and KAPA HiFi HotStart ReadyMix (Sigma-Aldrich, Shanghai, China), and the enriched library was sequenced on the HiSeq 4000 platform using a 2×150 bp sequencing kit [ 10 ]. (4) Sequencing data processing: Trimmomatic 25 software was used to filter the sequencing data and remove low-quality bases or N bases.…”
Section: Methodsmentioning
confidence: 99%
“…The most frequent cause of this chromosomal instability is a biallelic inactivation of BRCA1/2 genes in hereditary cancers [88][89][90]. BRCA1 and BRCA2 germ-line mutations predispose to breast, ovarian and possibly stomach malignancies [88,90,91]. In addition, BRCA2 pathogenic alleles are associated with increased risk of prostate and pancreatic carcinomas [92,93].…”
Section: Integrative Testsmentioning
confidence: 99%